Strengthening of Reinforced Concrete T-Beam with Web Opening - Hassan, Bedar Rauf; Abdul-Kadir, Mohamed Raouf; Ghafoor, Kawan Karem (Sulaimani Journal for Engineering Sciences, 2017)
This study examines shear capacity of strengthened reinforced concrete T-beams with web rectangular opening. Effect of opening orientation, presence of flange, different types of strengthening, and absence of shear reinforcement in strengthened beams are discussed and evaluated. The experimental work consisted of testing 13 beams under single point load. One of them considered as control beam without opening, while others are cast as beams with preplanned 100mm×200mm opening located at the web of the beam horizontally and vertically. The results of the beams indicated that the beams with horizontal openings show reduction in the ultimate shear capacity by about 17% while for vertical opening the reduction was about 27% compared to the control beam without opening .Moreover, the presence of the flange increased the shear capacity of the beams with horizontal and vertical openings by about 11% and 34.5% respectively. Also, the results indicated that the internal strengthening with inclined stirrups increased ultimate capacity by about 18% and 11% for horizontal and vertical openings compared to control T-beams with web opening respectively. The CFRP strips with spacing between them increased shear capacity by about 13.5% for horizontal opening but was not beneficial for vertical opening, also the CFRP strips for strengthening of opening made after construction were not beneficial for both types of opening and the capacity was decreased by about 11.5% and 10.1% for horizontal and vertical opening respectively. Strengthened beams with CFRP strips without spacing between them strengthened the bottom chord of the opening furthermore and they were best scheme of strengthening beam with vertical opening and increased shear capacity by about 12% for both types of opening.
Keywords: Reinforced Concrete T-Beam; Web Opening; CFRP Strengthening; Diagonal Reinforcement